APLIKASI SISTEM INFORMASI GEOGRAFIS (SIG) UNTUK PEMETAAN SEDIMENTASI SEBAGAI SALAH SATU UPAYA PELESTARIAN DAS WAMPU BAGIAN TENGAH DI PROVINSI SUMATERA UTARA - Marisi Intan Retno Widia Siahaan; Rahmawaty Rahmawaty; Abdul Rauf (Program studi Kehutanan USU, 2016)
Wampu Watershed is defined as the restored watershed carrying capacity according to Regulation of the Minister of Forestry of the Republic of Indonesia Number P.60 / Menhut-II / 2012. The land use for intensive agriculture is very dominant in Wampu watershed and increase the damage which is now often felt by the public. For that reason, that’s done a research for counting the suspended load that occured in Middle-stream of Wampu Watershed. The research was conducted on May up to September 2014 in Bahorok, Salapian, Kuala, and Selesai, by using survey method with taking sample randomly and continued by calculated of suspended load with United State Beureu Reclamation (USBR) method. Data processing used ArcView GIS 3.3. The results of this research showed that the highest suspended sediment discharged in middle-stream of Wampu watershed is 1.501.227,19 grams/second in Tanjung Lenggang, 324.625,29 grams/second in Empus, and 2.572,58 grams/second in Tanjung Keriahen. Therefore it’s necessary to control by doing an appropriate conservation measures to suppress the larger possibility of sedimentation. Keywords : Wampu watershed, Watershed conservation, sedimentation, USLE method, GIS